Immediate extraction-implantation and provisionalization (IIP): Esthetic evaluation of IIP surgical protocols via the Pink Esthetic Score: a retrospective cross-sectional study of 39 implants - Coiffic Syliane; Soulas Hugues; Hamon Julien (Journal of Oral Medicine and Oral Surgery)
A general protocol has been accepted by the scientific community for using the extraction immediate implantation and provisionalization (EIIP), in the replacement a compromised tooth in the antero-maxillary region, but the multiplicity of biomaterials used leads to diversity of application of the protocol. The aims of this study were to compare the Pink esthetic Score (PES) according to the EIIP protocol, evaluate abutment visibility according to surgical protocol, and assess whether the type of tooth rehabilitated had an impact on PES or abutment visibility. A retrospective study evaluating the PES of 39 implants in 3 treatment units compared the esthetic results of surgical techniques (xenogeneic graft, alloplastic, PRF, connective tissue graft, membrane) after the crown had been in use for at least 3 weeks. When indicated, EIIP treatment appears to be the treatment's choice for the management of compromised teeth in the antero-maxillary region, whatever the biomaterial used in the protocol (xenogeneic graft, platelet-rich fibrin, connective tissue graft, membrane, alloplastic substitute). Each of the PES observed was rated as “acceptable”, and no statistical differences were found in the study between biomaterials, tooth situation (central or lateral) or abutment visibility.